Principles and Design Scenarios for Sustainable Urban Food Logistics - Tochtrop, Christoph; Bickel, Manuel W.; Hennes, Lena; Speck, Melanie; Liedtke, Christa (Frontiers in Sustainable Cities, 2022)
Food and nutrition systems are linked to all Sustainable Development Goals (SDGs), which makes their transition towards social-ecological behavior patterns crucial for an overarching sustainability transformation. The perspective of (urban) logistics is of special interest. It couples the production and consumption physically and virtually. In this context, we shed light on the design of the turnover point of food in urban areas from the supply chain towards consumers and contribute to an overarching systemic perspective towards establishing a sustainable multilevel food system. We describe current patterns in urban food systems and propose several principles for sustainable design of (urban) food systems based on concepts such as (regional) collaboration and food literacy. Using these principles, we provide four design scenarios that concretely imagine future urban food consumption and production patterns titled “slow stock supply service”, “deliver into the daily walk”, “central district food depot”, “super food action place”. With this work we provide a starting for reflecting whether certain combinations of principles actually lead to patterns of daily life that are feasible, acceptable, or desirable. Moreover, we provide an initial qualitative assessment to stimulate further research that explores scenario pathways and incorporates additional indicators regarding the impact on social-ecological. We open up various research questions with regard to the overarching question of how urban food logistics should be designed to be consistent with the SDGs.